PERSPEKTIF ‘MISTIS’ DAN KONSTRUKSI SOSIAL RITUAL SEBLANG OLEHSARI (Lembaga Pengembangan Kinerja Dosen, 2023)
The researcher studied things including the Seblang ritual in the Olehsari village, Banyuwangi Regency, which tells about several occurrences of the Seblang ritual which was used as a symbol of 'rejecting balak' by the Olehsari community. The researcher explains several seblang ritual processes and the philosophy regarding the beginning of the seblang ritual which has been passed down from generation to generation from ancestors to grandchildren. The purpose of this research is to find out several things that must be explored in depth about Seblang cultural life. The emergence of the Seblang ritual began with a 'pagebluk' that attacked the slopes of Mount Ijen which resulted in many disasters such as sick people and many failed harvests. Remembering that traditional society in ancient times still believed in mystical things. Furthermore, there are several things that underlie the existence of the seblang ritual which is believed by the Olehsari community to ensure repulsion and protection from all existing disasters.